Urban Setting in Contemporary American Crime Fiction - Bubíková, Šárka (My University, 2022)
The article analyzes the changing representations of urban setting in contemporary American crime fiction. Briefly characterizing the traditional image of the city in American hardboiled crime fiction, it then moves on to contrast it with the way urban setting functions in many recent crime novels. Referring to crime series by Sara Paretsky, Linda Barnes, Laura Lippman, S.J. Rozan and Les Roberts, it analyzes how a new image of the city is constructed in contemporary crime writing. The article also tries to show that although the contemporary heightened interest in the role of places and spaces in literary works has been mainly focused on classic works or the so-called high-brow texts, it can yield interesting results when aimed at popular genres, such as crime fiction.
Město v současné americké detektivní próze
Keywords: crime fiction; urban setting; Sara Paretsky; Linda Barnes; Laura Lippman; S.J. Rozan; Les Roberts; detektivní próza; město; dějiště; Sara Paretsky; Linda Barnes; Laura Lippman; S.J. Rozan; Les Roberts